Assessment of sediment transport estimation methods in selected channels - Ali, Hydar Lafta (2015)
In this study, equations for estimating sediment transport in channels are assessed using field data of 15 rivers located at different part around the world, in which 14 are existing data and 1 is a new measured data. The new field data is for Al-Garraf river, Iraq measured using devices Son Tek River Surveyor (to measure hydraulic and geometric parameters), Van veen grab sampler (to collect bed materials), and Van Dron horizontal water bottle (to obtain suspended sediment load). Data sets related to other rivers is acquired from Brownlie (1981). The acquired data is widely used worldwide and known with its reliability. Several sediment transport equations have been computed and tested in order to recommend their accuracy. The tested equations include most river hydraulic and morphological characteristics. For bed load estimation in rivers, the results of computations show that there are variations of computed values with significant difference associated with applying Shield equation compare with other computed equations. The differences of computed values are referring to the concepts and methods of each equation. For estimation of suspended load, the results of comparisons show that Bagnold,Einstein and Van Rijin gave the least error in estimating the suspended load among the other tested equations. The least values of Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) are equal 0.012 and 0.015 (kg/s/m) respectively. It is found that this least error was associated with applying Bagnold equation. Moreover, an equation was proposed for computing suspended load in rivers based on the Einstein, Ackers and White, Shield parameters and Regression analysis. The coefficient of determination (R2) for proposed equation is found to be 0.80. The results obtained from applying the proposed equation show a reasonable performance when compared with other tested equations using field data for rivers Atchafalaya,Red, South American, Rio Grande, and Al-Garraf. The ranges of Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) are 0.005 to 0.007 and 0.09 to 0.289 (kg/s/m) respectively. The proposed equation is easy to apply compared with Einstein equation that requires complex procedure and longer time. The proposed equation will assist engineers to estimate suspended sediment load in natural rivers because it require short procedure and give a reasonable accuracy.